Advances in Signal Processing and Intelligent Recognition Systems 5th International Symposium, SIRS 2019, Trivandrum, India, December 18-21, 2019, Revised selected papers /: 5th International Symposium, SIRS 2019, Trivandrum, India, December 18-21, 2019, Revised selected papers. (2020) - Unknown
No abstract available